Update on the Role of Infection and Biofilms in Wound Healing: Pathophysiology and Treatment. (September 2016) - Gompelman, Michelle; van Asten, Suzanne A. V.; Peters, Edgar J. G.
Abstract : Background: Chronic wounds, and among these infected diabetic foot ulcers, are a worldwide problem. The poor treatment outcomes result in high healthcare costs, amputations, a decreased quality of life, and an increased mortality. These outcomes are influenced by several factors, including biofilm formation. A biofilm consists of pathogenic bacteria that are encased in an exopolysaccharide layer and communicate through secretion of signaling molecules. Bacteria that live in a biofilm are refractory to host responses and treatment. Methods: We performed a nonsystematic review of the currently published to-date medical biofilm literature. The review summarizes the evidence of biofilm in chronic wounds, the role of biofilm in wound healing, detection of biofilm, and available antibiofilm treatments. Articles containing basic science and clinical research, as well as systematic reviews, are described and evaluated. The articles have variable levels of evidence. All articles have been peer reviewed and meet the standards of evidence-based medicine. Results: Both animal and human studies have identified biofilm in chronic wounds and have suggested that healing might be influenced by its presence. A promising development in biofilm detection is rapid molecular diagnostics combined with direct microscopy. This technique, rather than classic culture, might support individualized treatment in the near future. A wide range of treatments for chronic wounds also influence biofilm formation. Several agents that specifically target biofilm are currently being researched. Conclusions: Biofilm formation has a substantial role in chronic wounds. Several diagnostic and therapeutic methods against biofilm are currently being developed.